Remote Laboratories in Engineering Education: Trends in Students' Perceptions - Lindsay, Euan; Liu, D.; Murray, S.; Lowe, D. (Australasian Association for Engineering Education, 2007)
Remotely accessible laboratories are an increasingly popular innovation in engineering education. Since 2001, The University of Technology, Sydney has implemented a number of remotely accessible laboratories. This paper presents an analysis of students' feedback responses to their use of the laboratories. The responses show that students not only appreciate the flexibility of the remote access option, but also that they feel that the remote option encourages them to take a deep learning approach to the material.